Women's education level amplifies the effects of a livelihoods-based intervention on household wealth, child diet, and child growth in rural Nepal - Laurie C. Miller; Neena Joshi; Mahendra Lohani; Beatrice Rogers; Shubh Mahato; Shibani Ghosh; Patrick Webb (BMC, 2017)
Abstract Background Many organizations seek to alleviate poverty in the developing world, often focusing their interventions on women. The role, status, and education of women are fundamentally important facets of development. Thus, understanding the interaction of women's educational level and the response to interventions is important. Therefore, we examined the impact of educational level of household adults on responses to a livestock-based community intervention. Methods Six pair-matched communities in 3 districts of Nepal (Chitwan/Nawalparasi/Nuwakot), were randomly assigned to receive community development activities via women's self-help groups at baseline or 1 year later. At 6 intervals over 48 months, a 125- item questionnaire addressing family demographics and child health/nutrition was completed in each household, plus child growth monitoring. Results were analyzed in relation to the highest education attained by any woman in the household, the child's mother, men, or any other adult in the household. Results Outcomes (wealth, water/toilet availability, child diet diversity and growth) all significantly related to adult education. However, notable differences were found comparing the impact of men's and women's education. Percent change in wealth score was significant only in households where women had primary or secondary education (respectively, p = .0009 and p < .0001). Increased soap use related only to women's education (p < .0001). When adjusted for group assignment, baseline income, wealth, and animal scores, higher women's education was significantly associated with increased household wealth (p < .0001), better child height-for-age z scores (HAZ, p = .005), and improved child diet diversity (p = .01). Higher mother's education predicted better child HAZ (primary, p = .01, secondary, p = .03) and diet diversity (primary, p = .05, secondary, p < .0001). Higher men's education was significantly associated with household wealth (p = .02) and child diet diversity (p = .04), but not HAZ; higher education of any household member was associated only with household wealth (p < .0001). Moreover, households where the mother's education was better than the best-educated man also were significantly more likely to have children with better HAZ and dietary diversity (p = .03, p < .0001). Thus, the educational level of women and mothers had the broadest impact on child outcome variables. Conclusions Household characteristics vary among participants in most community development projects. Of these, adult education likely mediates response to the inputs provided by the intervention. Particularly in interventions directed towards women, better education may enhance the ability of households to put interventions into practice, thus improving wealth, hygiene, and child diet and growth indices.